Treating short upper lip with "Unified lip repositioning" technique: Two case reports - Rahat Saleem; Bhavna Jha Kukreja; Manish Goyal; Mukesh Kumar (Wolters Kluwer Medknow Publications, 2022)
Excessive gingival display can be an esthetic concern for the patient. Conventional lip repositioning provides a conservative surgical option with less patient morbidity. The unified technique is a modification of conventional lip repositioning technique using the orthodontic brackets as anchorage to provide better soft-tissue closure with the lesser chances of relapse. This technique has been modified to be less invasive with better results. In this case report, patients undergoing orthodontic treatment with short upper lip were recommended for the surgical lip repositioning to reduce excess gingival display. Cases were treated with conventional lip repositioning technique and with unified lip repositioning technique, and after evaluation, comparison was done postoperatively. The unified lip repositioning technique showed better results with a significant decrease of gingival appearance and more patient compliance. Thus, in patients with short upper lip, unified lip repositioning technique can be a viable conservative treatment option.